2008
DOI: 10.1111/j.1365-2648.2008.04805.x
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of prenatal depression among Taiwanese women

Abstract: Prenatal depression is a painful growth experience represented by silent and unbalanced commitment during the maternal role transition. Our findings may help healthcare professionals to understand the vulnerable experiences of pregnant women and devise preventive intervention strategies, such as prenatal education for both parents and comprehensive screening for prenatal depression in at-risk pregnant women, so that they are better prepared for the transition to motherhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The most common risk factors for depressive symptoms during pregnancy are anxiety, perceived life stress, history of depression, lack of social support, unwanted pregnancy, low income, domestic violence, lack of education, smoking, and single marital status (Lancaster et al ., 2010). Of these, stress and social support are the psychosocial variables that have been most studied (Blaney et al ., 2004; Mann et al ., 2008; Tseng et al ., 2008; Furber et al ., 2009; Muzik et al ., 2009; Raymond, 2009; Reid et al ., 2009; Lancaster et al ., 2010). Other psychosocial variables that have been examined include quality of life, self‐esteem, religiosity, spirituality, fear of childbirth, locus of control, and coping strategies, such as disengagement and reframing (Blaney et al ., 2004; Jomeen, 2004; Jesse et al ., 2005; Jomeen & Martin, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common risk factors for depressive symptoms during pregnancy are anxiety, perceived life stress, history of depression, lack of social support, unwanted pregnancy, low income, domestic violence, lack of education, smoking, and single marital status (Lancaster et al ., 2010). Of these, stress and social support are the psychosocial variables that have been most studied (Blaney et al ., 2004; Mann et al ., 2008; Tseng et al ., 2008; Furber et al ., 2009; Muzik et al ., 2009; Raymond, 2009; Reid et al ., 2009; Lancaster et al ., 2010). Other psychosocial variables that have been examined include quality of life, self‐esteem, religiosity, spirituality, fear of childbirth, locus of control, and coping strategies, such as disengagement and reframing (Blaney et al ., 2004; Jomeen, 2004; Jesse et al ., 2005; Jomeen & Martin, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Records and Rice (2007) found that third trimester depression scores were significantly correlated with social support in a cross‐sectional examination of 139 pregnant women in the northwest USA. A lack of social support or emotional isolation was identified as a dominant theme among women who reported feeling “depressed” during pregnancy, and has been associated with increased psychological distress across cultures (Tseng et al ., 2008; Raymond, 2009). In Raymond's qualitative study, nine women recalled a lack of both physical and emotional support and felt uncomfortable confiding in health‐care providers, stating that the providers rarely saw the same patient and seemed more focused on the fetus.…”
Section: Resultsmentioning
confidence: 99%
“…Hsu and Chen17 found that the best predictors of depression during pregnancy were total stress, lack of social support, and unemployment. In Taiwan, Tseng et al24 examined the narratives of 12 Taiwanese women scoring above 15 on the EPDS. This group found that unbalanced commitment to motherhood was the primary theme in these 12 women.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there can be a risk of preterm birth and obstetric complications. And the newborns’ and husbands’ mental and physical health can also be threatened by their mothers’ and wives’ depression as well [916]. …”
Section: Introductionmentioning
confidence: 99%